Rien ne vaut le rouge - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Joseph Mawa Lufuku, du Centre de promotion sociale et agro-alimentaire (CEPROSA)